The psychology of suggestion - Stump, Lois (My University, 1903)
Introduction: Heredity and environment make the individual what he is. Heredity represents a mass of potent suggestions transmitted through the medium of “heredity-carriers” called gerni-plasmo which in uniting form the embryo of the human being. Environment may be defined as the suggestion to the maturing and educating self by surrounding influences. Suggestibility may be divided into two classes, that of suggestibility in the normal state of the individual or normal suggestibility and that of suggestibility in the abnormal state of the individual, or abnormal suggestibility. The soils favorable for the seeds of suggestion exist in the normal individual. The suggestible element is a constituent of our nature. Normal suggestibility though always with us rarely attracts our attention as it manifests itself in but trivial things. When, however it rises to the surface in great fury and cripples on its way every thing it can destroy, menace life and throws social order in the wildest state of confusion, we call it a mob. Deep down in the nature of man we find hidden the spirit of suggestibility. Man is often defined as a social animal; this is true, but it gives little insight into the psychical state of the individual composing the society. He has also been termed a rational animal but this scarcely holds true to all classes of men. It is not sociality nor rationality that best characterize the average specimen of mankind, but suggestibility, for man is a suggestible animal. This fact of suggestibility existing in the normal individual is of the utmost importance in the theoretical field of knowledge, in psychology, ethics, sociology, history as well as in practical life, politics, economics, and in education. For the work of this paper, however, the discussion will be confined mostly to that of suggestibility in the abnormal state or abnormal suggestibility, studying its relation to the subjective or hypnotic state and various other psychic phenomena.
Citation: Stump, Lois. The psychology of suggestion. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Stock Breeding; Heritibility; Charles Darwin; Theses